Proceedings of the International Conference on Advanced Research in Electronics and Communication Systems (ICARECS 2025) - A. Shirly Edward; Rahul Krishnan; P. Nagarajan; M I Anju; Muzammil Bin Jusoh (Atlantis Press International BV, 2025)
This open access volume presents the select proceedings of International Conference on Advanced Research in Electronics and Communication Systems (ICARECS-2025). Various topics covered in this volume are Artificial Intelligence, 5G Technology and Implementations, MIMO and Multi-antenna communications, Internet-of-Things / Devices, Cognitive and Software-Deﬁned Radio, Biomedical Signal Processing, Signal Processing for Communications, VLSI Signal Processing, Radar and Sonar Signal Processing, Speech Processing and Recognition Cryptography, Security and Privacy algorithms, AI-powered Smart Electronics, 6G and Beyond: Emerging Technologies and Applications, Cloud-Based Networks, Low-Power Wide-Area Networks (LPWAN) for IoT, Machine Learning in Communication Systems, Blockchain for Secure and Transparent Communication, Artificial Intelligence for Network Optimization, etc.